Increase in serogroup W invasive meningococcal disease in England associated with pilgrimage to Saudi Arabia, January 2024 to June 2025 - Shamez N Ladhani (Eurosurveillance)
England is experiencing an increase in serogroup W invasive meningococcal disease (IMD) caused by ‘strain A’ of the meningococcal sequence type 11 clonal complex (MenW:cc11) Hajj strain sublineage. Travel-associated and non-travel-associated meningococci from four strain A substrains (A1–A4) accounted for 32 of 59 MenW IMD cases between January 2024 and June 2025, 14 in people returning from Saudi Arabia or household contacts; eight of 14 linked to Umrah pilgrimage. Communications about MenACWY vaccination for pilgrims year-round should be reinforced.